2019
DOI: 10.1097/ccm.0000000000003635
|View full text |Cite
|
Sign up to set email alerts
|

Dysglycemia and Neurologic Outcome in Mechanically Ventilated Patients With Guillain-Barré Syndrome

Abstract: Objectives: Acute respiratory failure is a frequent complication of Guillain-Barré syndrome, associated with high morbidity and mortality. Adjuvant treatments are needed to improve the outcome of Guillain-Barré syndrome. Since dysglycemia is a risk factor for development of axonal polyneuropathy in critically ill patients and since insulin therapy may be neuroprotective, we sought to explore the association between dysglycemia and neurologic status in Guillain-Barré syndrome patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Higher levels of fasting plasma glucose are frequently observed in patients with cranial nerve involvement, autonomic deficit, dyspnea, and ventilator dependence, which are associated with a poorer short-term prognosis at discharge ( Wang et al, 2015a ). Moreover, dysglycemia was closely correlated with a neurologic disability at ICU discharge and may delay motor recovery in MV-dependent patients ( Polito et al, 2019 ). A tight glycemic control results in reduced morbidity and mortality of surgical, medical, and pediatric ICU patients ( Van Den Berghe et al, 2001 ; Van Den Berghe et al, 2006 ; Vlasselaers et al, 2009 ).…”
Section: Supportive Care and Treatment In The Intensive Care Unitmentioning
confidence: 99%
“…Higher levels of fasting plasma glucose are frequently observed in patients with cranial nerve involvement, autonomic deficit, dyspnea, and ventilator dependence, which are associated with a poorer short-term prognosis at discharge ( Wang et al, 2015a ). Moreover, dysglycemia was closely correlated with a neurologic disability at ICU discharge and may delay motor recovery in MV-dependent patients ( Polito et al, 2019 ). A tight glycemic control results in reduced morbidity and mortality of surgical, medical, and pediatric ICU patients ( Van Den Berghe et al, 2001 ; Van Den Berghe et al, 2006 ; Vlasselaers et al, 2009 ).…”
Section: Supportive Care and Treatment In The Intensive Care Unitmentioning
confidence: 99%
“…( 16 ). Other authors have reported that worse neurological status with disability at ICU discharge correlated with dysglycemia in mechanically ventilated Guillain-Barré syndrome patients ( 26 ). In this study, we found a similar observation that hyperglycaemia and increase of CRP at admission were positively associated with mechanical ventilation.…”
Section: Discussionmentioning
confidence: 97%